The Rad5 Helicase and RING Domains Contribute to Genome Stability through their Independent Catalytic Activities. Issue 5 (15th March 2022) - Toth, Robert; Balogh, David; Pinter, Lajos; Jaksa, Gabor; Szeplaki, Bence; Graf, Alexandra; Gyorfy, Zsuzsanna; Enyedi, Marton Zs.; Kiss, Erno; Haracska, Lajos; Unk, Ildiko
Graphical abstract: Highlights: The enzymatic contribution of the Rad5 helicase domain to DNA damage bypass is debated. The Rad5 RING and helicase domains can function independent of each other. Lack of Rad5 leads to minor changes in the spectrum of mutagenesis. The results delineate the contribution of Rad5 to DNA damage tolerance. Abstract: Genomic stability is compromised by DNA damage that obstructs replication. Rad5 plays a prominent role in DNA damage bypass processes that evolved to ensure the continuation of stalled replication. Like its human orthologs, the HLTF and SHPRH tumor suppressors, yeast Rad5 has a RING domain that supports ubiquitin ligase activity promoting PCNA polyubiquitylation and a helicase domain that in the case of HLTF and Rad5 was shown to exhibit an ATPase-linked replication fork reversal activity. The RING domain is embedded in the helicase domain, confusing their separate investigation and the understanding of the exact role of Rad5 in DNA damage bypass. Particularly, it is still debated whether the helicase domain plays a catalytic or a non-enzymatic role during error-free damage bypass and whether it facilitates a function separately from the RING domain. In this study, through in vivo and in vitro characterization of domain-specific mutants, we delineate the contributions of the two domains to Rad5 function. Yeast genetic experiments and whole-genome sequencing complemented with biochemical assays demonstrate that the ubiquitin ligase and the ATPase-linked activities of Rad5 exhibit independent catalytic activities in facilitating separate pathways during error-free lesion bypass. Our results also provide important insights into the mutagenic role of Rad5 and indicate its tripartite contribution to DNA damage tolerance.